Knockdown of Zebrafish Blood Vessel Epicardial Substance Results in Incomplete Retinal Lamination. (6th March 2014) - Wu, Yu-Ching; Chen, Ruei-Feng; Liu, Chia-Yang; Hu, Fung Rong; Huang, Chang-Jen; Wang, I-Jong
Abstract : Cell polarity during eye development determines the normal retinal lamination and differentiation of photoreceptor cells in the retina. In vertebrates, blood vessel epicardial substance (Bves) is known to play an important role in the formation and maintenance of the tight junctions essential for epithelial cell polarity. In the current study, we generated a transgenic zebrafish Bves ( zbves ) promoter-EGFP zebrafish line to investigate the expression pattern of Bves in the retina and to study the role of zbves in retinal lamination. Immunostaining with different specific antibodies from retinal cells and transmission electron microscopy were used to identify the morphological defects in normal and Bves knockdown zebrafish. In normal zebrafish, Bves is located at the apical junctions of embryonic retinal neuroepithelia during retinogenesis; later, it is strongly expressed around inner plexiform layer (IPL) and retinal pigment epithelium (RPE). In contrast, a loss of normal retinal lamination and cellular polarity was found with undifferentiated photoreceptor cells in Bves knockdown zebrafish. Herein, our results indicated that disruption of Bves will result in a loss of normal retinal lamination.